Importance of research in organizations. By Fernando Salgado (GEON Journal (Management, Organizations and Business), 2013)
The study of organizations, their environment and trends, are a fundamental part in the generation of growth and economic development. The schools of the administrative thought, contribute postulates that are susceptible of analysis; Likewise, the current dynamics of business, technological advances, the development of telecommunications, the globalization of the economy and the insertion of companies in international markets have generated a greater spectrum that contributes to the strengthening of organizational research in order to identify elements of judgment that allow inference regarding the performance of companies.
Keywords: Investigation; Organization; Corporate culture; Competitiveness; Leadership; Organizational development